In vivo molecular neuroimaging of glucose utilization and its association with fibrillar amyloid-β load in aged APPPS1-21 mice. Issue 1 (December 2015) - Waldron, Ann-Marie; Wintmolders, Cindy; Bottelbergs, Astrid; Kelley, Jonathan; Schmidt, Mark; Stroobants, Sigrid; Langlois, Xavier; Staelens, Steven
Abstract Introduction Radioligand imaging is a powerfulin vivo method to assess the molecular basis of Alzheimer's Disease. We therefore aimed to visualize the pathological deposition of fibrillar amyloid-β and neuronal dysfunction in aged double transgenic mice. Methods Using non-invasive positron emission tomography (PET) we assessed brain glucose utilization with [18 F]FDG and fibrillar amyloidosis with [11 C]PiB and [18 F]AV45 in 12 month old APPPS1-21 (n = 10) mice and their age-matched wild-type controls (n = 15). PET scans were analyzed with statistical parametric mapping (SPM) to detect significant differences in tracer uptake between genotypes. After imaging, mice were sacrificed andex vivo measures of amyloid-β burden with immunohistochemistry as well as glucose utilization with [14 C]-2DG autoradiography were obtained as gold standards. Results Voxel-wise SPM analysis revealed significantly decreased [18 F]FDG uptake in aged APPPS1-21 mice in comparison to WT with the thalamus (96.96 %, maxT = 3.35) and striatum (61.21 %, maxT = 3.29) demonstrating the most widespread reductions at the threshold ofp < 0.01. [11 C]PiB binding was significantly increased in APPPS1-21 mice, most notably in the hippocampus (87.84 %, maxT = 7.15) and cortex (69.08 %, maxT = 7.95), as detected by SPM voxel-wise analysis at the threshold ofp < 0.01. Using the same threshold [18 F]AV45 uptake was comparably lower with less significant differences. Compared to their respectiveex vivo equivalents [18 F]FDG demonstrated significant positive correlation to [14 C]2-DG autoradiography (r = 0.67, p <0.0001) while [11 C]PiB and [18 F]AV45 binding did not correlate toex vivo immunohistochemistry for amyloid-β (r = 0.25, p = 0.07 and r = 0.17, p = 0.26 respectively). Lastly no correlation was observed between regions of high amyloid burden and those with decreased glucose utilization (r = 0.001, p = 0.99). Conclusions Our findings support that fibrillar amyloid-β deposition and reduced glucose utilization can be visualized and quantified within vivo μPET imaging in aged APPPS1-21 mice. Therefore, the combined use of [18 F]FDG and amyloid μPET imaging can shed light on the underlying relationship between fibrillar amyloid-β pathology and neuronal dysfunction.